Rapid evolution of an invasive weed. Issue 1 (10th December 2013) - Turner, Kathryn G.; Hufbauer, Ruth A.; Rieseberg, Loren H.
Summary: Trade‐offs between performance and the ability to tolerate abiotic and biotic stress have been suggested to explain both the success of invasive species and phenotypic differentiation between native and invasive populations. It is critical to sample broadly across both ranges and to account for latitudinal clines and maternal effects when testing this premise. Wild‐collected Centaurea diffusa seeds were grown in benign and stressful conditions (drought, flooding, nutrient stress and simulated herbivory), to evaluate whether native and introduced individuals differ in performance or life history phenotypes. A second experiment used glasshouse‐grown seeds to evaluate whether patterns remain comparable when maternal environment is consistent. Many traits differed between ranges, and in all cases but one, invasive individuals grew larger, performed better, or matured later. No trade‐off in performance with herbivore defense was evident. Invasive populations may have been released from a trade‐off between growth and drought tolerance apparent in the native range. Larger individuals with delayed maturity and greater reproductive potential have evolved in invasive populations, a pattern evident across broad population sampling, and after latitude and maternal environment were considered. Release from abiotic stress tolerance trade‐offs may be important for the invasion success of Centaurea diffusa .